Associations between HIV Status Disclosure, Social Support, and Adherence to and Antiretroviral Therapy in Adults Patients with HIV/AIDS - Mustainu Habibi; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2021)
Background: Antiretroviral therapy (ART) has been successful in increasing the life span and quality of life of people living with HIV. The success of antiretroviral treatment can be assessed from the patient's compliance in taking the drugs prescribed by the doctor at the right time and at the right dose. Disclosure of HIV status and social support are factors associated with adherence to antiretroviral therapy (ART). This study aims to estimate the magnitude of disclosure of HIV status and social support with antiretroviral therapy adherence to adult patients with HIV/AIDS with a meta-analysis study. Subjects and Method: This was a systematic review and meta-analysis conducted using PRISMA flow diagrams. Article searches were conducted through journal databases including: Google Scholar, PubMed, Springer Link, Clinical key and ProQuest. The articles used in this study are articles that have been published from 2010-2021. The keywords to search for articles are as follows: